Phenology of Talauma gloriensis Pittier (Magnoliaceae), Alberto Manuel Brenes Biological Reserve, San Ramón, Alajuela, Costa Rica - Brenes Cambronero, Liz (2017)
Phenology of the tree species Talauma gloriensis was studied from March 2014 to 0ctober 2015.  This species has averaged 16.6 m high in the Alberto Manuel Brenes Biological Reserve forest, Alajuela, Costa Rica. Eight mature trees were marked in order of appearance and observed every month using binoculars. Leaf abscission and budding were continuous throughout the research, while flowering and fruit production occurred in small periods throughout the year, this species is subannual.  Fruiting was correlated with air temperature (n = 8, r = 0.86, p < 0.05), and precipitation (n = 8, r = 0.54, p < 0.05).  Bud formation was inversely associated with precipitation (n = 8, r = -0.42, p < 0.05) and air temperature (n = 8, r = -0.80, p < 0.05), and flowering was associated with air temperature (n = 8, r = -0.91, p < 0.05).